Literature Review on Diabetes Internet-based Spanish-Language Information - Aponte, Judith; Tejada, Karen; Acosta-Melo, Mariel (Current Diabetes Reviews, 2018)
Background: Diabetes is a growing epidemic that is affecting Hispanics in high rates. Introduction: Although Hispanics use the internet for health-related informational and educational purposes, there is a lack of information available in the Spanish-language. Methods: A review was conducted to examine the literature on internet-based, Spanish-language, diabetes focused information. One search was conducted using three different databases (i.e. CINAHL, MEDLINE, and PubMed). The search used the keywords diabetes, internet, and Spanish, and was based on published articles from January 1, 2005 to June 30, 2016. Results: Of the 46 articles reviewed, one was a duplicate, and 41 were eliminated. These findings show a lack of data and research on Spanish-language, internet-based diabetes informational and educational sites. Conclusion: Qualitative and quantitative studies are needed to develop and examine Spanish-language diabetes internet sites and the health-related impact they have on Hispanics who prefer Spanishlanguage sites.
Keywords: internet-based sites